Issues related to biblical names in Judaism and Christianity - Perzyński, Andrzej Piotr (Name – style – text: A jubilee book dedicated to Professor Elżebieta Umińska-Tytoń, 2023)
The article Issues related to biblical names in Judaism and Christianity consists of the following parts: 1. Historical outline; 2. Old Testament or Hebrew Bible?; 3. Old Testament languages; 4. Ancient Bible translations; 5. Significance of Apocrypha; 6. Hebrew Bible / Old Testament in Judaism and Christianity; 6.1 Three-part division of the Hebrew Bible and its significance; 6.2. issues related to understanding and authority; Ending. Issues related to the names in the Bible were analyzed from three perspectives: texts language; existence of ancient translations and question of collection content. The intention of the author was to present how today various religious communities (Christian churches and synagogue) perceive the same materials through various prisms, in different canonical orders, in different languages and with different emphases. Those differences are not the foundation for arguments who understands the text correctly. They point out to the text richness, interpretative traditions and human imagination.